Morphometric Study of the Length and the Breadth of the Scapula in a Bangladeshi Population - Latif, Md Safat; Epsi , Effat Zerin; Shanto, Rafuja Afrin; Haque, Shah Md Atiqul; Sultana, Masuma; Biswas, Tithi Rani; Shom, Tumpa; Chaity, Chitra Dey; Bhuiyan, Sadia (Community Based Medical Journal, 2025)
A cross-sectional, descriptive study was carried out in the Department of Anatomy, Mymensingh Medical College, Bangladesh, from January to December of 2019, to see the variation in length and breadth of human scapulae. We adopted a convenient sampling technique. A total of 150 fully ossified dry human scapulae (70 right sided and 80 left sided) of Bangladeshi people were collected. Any kind of damaged or broken scapulae were excluded. The length and breadth were measured using a digital Vernier slide calipers. The length of the scapula was measured by the distance between the summit of the superior angle and the inferior angle of the scapula, while the breadth was measured by the distance between the spine intersecting the medial border of the scapula and the lower point of outer border of the glenoid cavity. Scapular index was determined by dividing its breadth by its length and multiplied by 100. The mean lengths of the right and left sided scapulae were found 136.59±12.04 mm and 136.37±12.92 mm respectively. The mean breadths of the right and left sided scapulae were found 100.13±8.19 mm and 99.9±7.66 mm respectively. The mean scapular indexes were found 73.17±3.66 and 73.41±3.91 for the right and the left side respectively. Our findings are important racial comparison that could contribute to anthropological studies as well as in clinical settings for innovative prosthesis design for the surgeries of shoulder joint. CBMJ 2025 July: vol. 14 no. 02 P:141-145